P Pendapatan Usahatani Kelapa Sawit di Desa Pole Maju Jaya, Kecamatan Poli-Polia, Kabupaten Kolaka Timur - Irmawatty Paula Tamburaka; La Tondi La Tondi; Sabrina Sabrina (Jurnal Multidisipliner Bharasumba, 2026)
This study aims to analyze the income and the factors affecting oil palm farming income in Pole Maju Jaya Village. A total of 45 oil palm farmers were selected as respondents using purposive sampling with the Slovin formula. Primary and secondary data were collected through surveys, interviews, and documentation. Data were analyzed using farm income analysis and multiple linear regression. The results show that the average net income of oil palm farmers was IDR 5,020,518 per harvest season, indicating that oil palm farming provides a profitable source of income. Regression analysis reveals that land size has no significant effect on farmers' income, whereas maintenance costs have a positive and significant effect. Simultaneously, land size and maintenance costs significantly influence farmers' income, with the model explaining 86.3% of the variation in income.